2020
DOI: 10.1002/jcu.22925
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of the elasticity of the ascending aorta in patients with essential hypertension

Abstract: Background: Hypertension is the most common chronic disease and the most important risk factor for cardiovascular and cerebrovascular diseases. Atheroma and arteriosclerosis plays a key role in the occurrence and development of hypertension. The purpose of this study was to evaluate the elasticity of ascending aorta wall in patients with essential hypertension (EH) using M-mode echocardiography.Materials and Methods: We prospectively enrolled 54 EH patients and 51 healthy subjects (HS). They all underwent tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The T2DM group had considerably lower AC, AD, and AS indices than did the comparison group but had higher ASI and AEM. This study successfully reproduced the findings previously reported by Malgorzata Dec-Gilowska et al [17]. Furthermore, our findings are consistent with those of Liu et al, who conducted a study on individuals with diabetes patients and concluded that these patients are more likely to experience arterial stiffness than healthy individuals are [25].…”
Section: Comparison Of Aortic Elasticity Indices Between Patients Wit...supporting
confidence: 93%
See 2 more Smart Citations
“…The T2DM group had considerably lower AC, AD, and AS indices than did the comparison group but had higher ASI and AEM. This study successfully reproduced the findings previously reported by Malgorzata Dec-Gilowska et al [17]. Furthermore, our findings are consistent with those of Liu et al, who conducted a study on individuals with diabetes patients and concluded that these patients are more likely to experience arterial stiffness than healthy individuals are [25].…”
Section: Comparison Of Aortic Elasticity Indices Between Patients Wit...supporting
confidence: 93%
“…and aortic Peterson's elastic modulus (AEM) mmHg = [(SBP -DBP) x AoD]/(AoS -AoD). Note: AoS refers to the aortic end-systolic diameter; AoD denotes the aortic end-diastolic diameter; SBP represents systolic blood pressure; DBP stands for diastolic blood pressure [16][17][18].…”
Section: Arterial Stiffness Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found a negative correlation between the CS and pulse wave velocity. In addition, some investigators assessed aortic elasticity via M-mode echocardiography or tissue Doppler imaging (TDI) in hypertensive patients, demonstrating that hypertensive patients have reduced aortic elasticity (22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a signi cant correlation between VVI parameters and the aortic elastic parameters D and SI. D and SI have been proven to re ect changes in aortic elasticity in many studies (22,23,27) . These ndings indicate that VVI could sensitively and directly re ect the elasticity of the vascular wall in evaluating early aortic biomechanical dysfunction.…”
Section: Discussionmentioning
confidence: 99%